Labour, politics, and the state in industrializing Thailand - Brown, Andrew, 1953- (RoutledgeCurzon, 2004)
This book focuses on how the state has become entangled in the processes through which workers have been organized, reorganized and disorganized as social and political actors in different historical periods.
Keywords: Working class -- Thailand -- History -- 20th century.; Labor unions -- Thailand -- History -- 20th century.; Labor unions -- Political activity -- Thailand -- History -- 20th century.; Industrialization -- Thailand -- History -- 20th century.; Travailleurs -- Thaïlande -- Histoire -- 20e siècle.; Syndicats -- Thaïlande -- Histoire -- 20e siècle.; Syndicats -- Activité politique -- Thaïlande -- Histoire -- 20e siècle.; Industrialisation -- Thaïlande -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Political Process -- Political Advocacy.; Industrialization; Labor unions; Labor unions -- Political activity; Working class; Thailand; 1900-1999; Electronic books.; History